2014
DOI: 10.1161/jaha.113.000723
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Necrosis Factor‐Like Weak Inducer of Apoptosis or Fn14 Deficiency Reduce Elastase Perfusion‐Induced Aortic Abdominal Aneurysm in Mice

Abstract: BackgroundAbdominal aortic aneurysm (AAA) involves leukocyte recruitment, inflammatory cytokine production, vascular cell apoptosis, neovascularization, and vascular remodeling, all of which contribute to aortic dilatation. Tumor necrosis factor‐like weak inducer of apoptosis (TWEAK) is a cytokine implicated in proinflammatory responses, angiogenesis, and matrix degradation but its role in AAA formation is currently unknown.Methods and ResultsExperimental AAA with aortic elastase perfusion in mice was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…TWEAK/Fn14 interaction also augments chemokines expression and secretion by both vascular smooth muscle cells (VSMCs) and macrophages [3,5]. In addition, TWEAK also induces metalloproteinase 3 and 9 activity in both VSMCs and macrophages, favoring plaque instability [5,6]. On the other hand, in vivo experiments have demonstrated that TWEAK participates in development, progression and ultimate rupture of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TWEAK/Fn14 interaction also augments chemokines expression and secretion by both vascular smooth muscle cells (VSMCs) and macrophages [3,5]. In addition, TWEAK also induces metalloproteinase 3 and 9 activity in both VSMCs and macrophages, favoring plaque instability [5,6]. On the other hand, in vivo experiments have demonstrated that TWEAK participates in development, progression and ultimate rupture of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…TWEAK/Fn14 interaction could participate in different processes associated with atherosclerotic plaque development such as proliferation and migration of vascular cells, and angiogenesis, inflammation and thrombosis. In fact, experimental studies have demonstrated that TWEAK participates in atherosclerotic plaque development, progression and rupture [3e5], and contributes to susceptibility for developing abdominal aortic aneurysm [6]. In addition, persistent TWEAK/Fn14 activation/ inactivation mediated by blocking or overexpression experiments in animal models has shown an important role of this axis in several pathologies such as stroke, heart failure and myocardial infarction, among others [7e9].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown a key role of the TWEAK-Fn14 axis in atherosclerotic plaque development, progression, and rupture (5-7). Moreover, specific gain-or loss-of-function phenotypes have shown that TWEAK participates in the development of experimental abdominal aortic aneurysms, stroke, myocardial infarction, and heart failure (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In the arterial wall, TWEAK is expressed in both healthy arteries and atherosclerotic plaques10. However, Fn14 expression is low or absent in normal arteries but is highly upregulated under pathological conditions including atherosclerotic plaques and abdominal aortic aneurysm of both, murine and human origin10111213. TWEAK is involved in different steps associated with vascular remodeling such as endothelial dysfunction, inflammation, proliferation and migration of VSMCs, angiogenesis and thrombosis141516.…”
mentioning
confidence: 99%